Metamodel-based Optimization of a PID Controller Parameters for a Coupled-tank System - Marwan Nafea; Abdul Rasyid Mohammad Ali; Jeevananthan Baliah; Mohamed Sultan Mohamed Ali (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Liquid flow and level control are essential requirements in various industries, such as paper manufacturing, petrochemical industries, waste management, and others. Controlling the liquids flow and levels in such industries is challenging due to the existence of nonlinearity and modeling uncertainties of the plants. This paper presents a method to control the liquid level in a second tank of a coupled-tank plant through variable manipulation of a water pump in the first tank. The optimum controller parameters of this plant are calculated using radial basis function neural network metamodel. A time-varying nonlinear dynamic model is developed and the corresponding linearized perturbation models are derived from the nonlinear model. The performance of the developed optimized controller using metamodeling is compared with the original large space design. In addition, linearized perturbation models are derived from the nonlinear dynamic model with time-varying parameters.